971. PECTEILIS SUSANNAE: Orchidaceae. (29th April 2021) - Wah, Lee Kit; Kumar, Pankaj; Gale, Stephan W.
Summary: Viable populations of threatened orchids can be re‐established in the wild through integrated conservation that combines a scientific understanding of species ecology with applied knowledge of horticultural requirements. Previously abundant in South China, Pecteilis susannae has declined due to habitat loss and collection, both for its magnificent flowers and its fleshy tubers, which are of purported medicinal value. To illustrate the steps being taken for the conservation of this and other orchids in Hong Kong, the history, taxonomy and ecology of P. susannae are discussed, and information on its propagation and culture are provided.